Technology in Digital Economy: How Effective Technology Enhance Sectoral Contributions in Indonesia? - Abilio da Costa; Nurul Ilmy; Oktavianty; Alamsyah Agit (www.amertainstitute.com, 2024)
Economic growth is an achievement that is the goal of many sectors, especially the economic sector, as these sectors will contribute to a region's economy. The digital era is an era that highlights innovation and advanced technology that has been widely used in various sectors, generally driving a significant increase in sector performance. However, in its application, technology implementation and innovation creation often need to be improved by various challenges. To find out the various challenges that hinder digital transformation, an in-depth analysis is needed in various sectors, which will be the main objective of this study. This study is qualitative with a literature study approach; the data collected comes from various research articles and review articles published in the last ten years. The data analysis used is deductive reasoning to extract information relevant to the theme raised in this study. The results of this study indicate that one of the sectors with the most significant contribution in Indonesia is the processing industry; as one of the largest sectors, the processing industry is one of the sectors that has implemented the use of technology and automation in its operational activities. On a small scale, many home industries have been able to use technology in marketing activities to reach more consumers. Some others need help understanding the use of technology, so they prefer to continue operating conventionally without using technology, causing an imbalance in sales. However, the contribution of the processing industry sector in general is supported by the implementation of technology, which also affects other sectors that contribute significantly to the economy, such as construction and trade.